2015
DOI: 10.5539/gjhs.v7n6p258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eye Movement Desensitization and Reprocessing (EMDR) on Depression in Patients With Myocardial Infarction (MI)

Abstract: Background:Coronary heart disease is the most important cause of death and inability in all communities. Depressive symptoms are frequent among post-myocardial infarction (MI) patients and may cause negative effects on cardiac prognosis. This study was conducted to identify efficacy of EMDR on depression of patients with MI.Methods:This study is a clinical trial. Sixty patients with MI were selected by simple sampling, and were separated randomly into experimental and control groups. To collect data, demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 9 publications
(7 reference statements)
0
26
0
5
Order By: Relevance
“…Other studies used a similar therapy, but on patients with various types of diseases. For instance, Behnammoghadam et al conducted a clinical trial on sixty patients with myocardial infarction. The EMDR intervention in three sessions lasting for 45 to 90 minutes in four consecutive months led to the reduction of patients’ depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies used a similar therapy, but on patients with various types of diseases. For instance, Behnammoghadam et al conducted a clinical trial on sixty patients with myocardial infarction. The EMDR intervention in three sessions lasting for 45 to 90 minutes in four consecutive months led to the reduction of patients’ depression.…”
Section: Discussionmentioning
confidence: 99%
“…Schneider et al stated that EMDR was an important treatment for the reduction of depression and anxiety. Behnammoghadam et al and Hase et al reported statistically significant reductions in the depressive symptoms of patients after the use of EMDR. Staring et al compared the effects of EMDR and competitive memory training (COMET), that were used in combination in patients with anxiety (n = 47).…”
Section: Introductionmentioning
confidence: 96%
“…Certaines s'appuient beaucoup sur un travail corporel (relaxation corporelle, techniques de respiration, sophrologie, training autogène) ;d 'autres sont plus psychiques (hypnose ericksonnienne, thérapies cognitivo-comportementales ou TCC, méditation en pleine conscience) ;e n fi n, certaines sont mixtes comme la cohérence cardiaque ou l'EMDR (Eyes Motion Desensitization and Reprocessing). Les thérapies curatives les mieux validées sont les TCC [70][71][72][73], la méditation en pleine conscience [74,75] et l'EMDR, particulièrement dans la prise en charge du syndrome de stress post-traumatique [76].…”
Section: La Prise En Chargeunclassified
“…Begitu pula dengan hasil temuan Korn (2009) yang menemukan bahwa EMDR lebih cepat memberikan efek dari pada exposure therapy dalam menangani trauma. Hal lain yang turut merangsang ide untuk mengulas EMDR sebagai penanganan PTSD adalah EMDR telah banyak dijadikan sebagai bahan penelitian di berbagai bidang, misalnya efektif dalam menurunkan kecemasan patologis pada penderita Generalized Anxiety Disorder (Farima, Dowlatabadi, & Behzadi, 2015), berguna dalam penanganan masalah gangguan obsesif-kompulsif (Böhm & Voderholzer, 2010), mampu menangani dan menurunkan depresi (Moghadam, Moghadam, & Salehian, 2015), mengurangi stres akademik (Henrikus, 2015), menurunkan kecemasan pada korban penganiayaan (Tarquinio et al, 2012), efisien bagi ahli klinis dalam mengakses simptom fisiologis dan psikologis yang mempengaruhi pengembangan kehidupan individu (Shapiro, 2014), mampu menurunkan trauma pada anak-anak (Rodenburg et al, 2009) serta mampu menurunkan simptom trauma secara signifikan (Sack, Lempa, & Lamprecht, 2007).…”
unclassified